065. Ileoileal Small Bowel Intussusception in Adult - Angwarmase, Alfonsa; Wijaya, Alma (JBN (Jurnal Bedah Nasional), 2024)
Background : Intestinal Intussusception is invagination of a proximal segment of the gastrointestinal tract into the distal. In adults, ileoileal intussusception is a rare case and diagnostically challenging. We present four cases of ileoileal small bowel intussusception in adults. Case : a 19-year-old man with complaint of abdominal pain. An exploratory laparotomy was performed, an ileoileal invagination was found. Second case : a 29-year-old woman with complaint of not being able to defecate or flatus. An ileal dilatation up to 240 cm from the ligament of treitz and ileoileal invagination with an ileal tumor was found in exploratory laparotomy. Third case : a 51-year-old man with complaint of difficulty defecating since 1 day before admission. A 30 cm long ileoileal invagination and tumor in the invaginated ileum was found. Fourth case : a 77-year-old man with a difficulty in defecating. A dilatation of the bowel starting from jejunum-ileum and a 20 cm long invagination was found. Conclusion: Clinical presentation of bowel obstruction is helpful to diagnose adult ileoileal small bowel intussusception. The mainstay of treatment is surgical intervention.